Ionospheric response to CIR‐induced recurrent geomagnetic activity during the declining phase of solar cycle 23. Issue 2 (16th February 2015) - Chen, Yanhong; Wang, Wenbin; Burns, Alan G.; Liu, Siqing; Gong, Jiancun; Yue, Xinan; Jiang, Guoying; Coster, Anthea
Abstract This paper presents an epoch analysis of global ionosphere responses to recurrent geomagnetic activity during 79 corotating interaction region (CIR) events from 2004 to 2009. The data used were GPS total electron content (TEC) data from the Madrigal Database at the Massachusetts Institute of Technology Haystack Observatory and the electron density (Ne) data obtained from CHAllenging Minisatellite Payload (CHAMP) observations. The results show that global ionosphere responses to CIR events have some common features. In high and middle latitudes, the total electron content (TEC) showed a significant positive response (increased electron densities) in the first epoch day. A negative TEC response occurred at high latitudes of the American sector following the positive response. The CHAMP Ne showed a daytime positive response in all latitudes and a nighttime negative response in the subauroral region. These negative TEC and Ne responses were found to be related to thermospheric composition (O/N2) changes during the storms. At all latitudes, the maximum of the TEC positive effect always occurred at 2–6 h after the CIR starting during local daytime and 10–18 h later for the CIR onset during local nighttime. Case studies indicate that the TEC and Ne positive response had a strong dependence on the southward component (Bz) of the interplanetary magnetic field and solar wind speed. This suggests that penetration electric fields that were associated with changes in solar winds might play a significant role in the positive ionospheric response to storms. During the recovery time of the CIR‐produced geomagnetic activity, the TEC positive disturbance at low latitudes sometimes could last for 2–4 days, whereas at middle to high latitudes the disturbance lasted only for 1 day in most cases. A comparison of the ionospheric responses between the American, European and Asian sectors shows that the ionosphere response in the North American sector was stronger than that in the other two regions. The response of foF2 to the CIR events in middle to high latitudes showed a negative response for 2–3 days after the first epoch day. This is different from the response of TEC, which was mostly positive during the same period of time.